Web Development of SIPARDI as a Digital Archive Storage Information System at SMA Jenderal Sudirman Kalipare - Azis, Muhammad Abdul Mughni; Antero, Nailah Aliya Putri; Yunizar, Ramadhani Eva; Lestari, Rizka Febry; Ferdiansyah, Riza Yahya; Putri, Ovitadani Mawaddah; Sumarsono, Raden Bambang; Wibowo, Wahyu Adi Setyo (Universitas Negeri Malang, 2024)
The development of the SIPARDI Web (Digital Archive Storage Information System) aims to increasethe efficiency and effectiveness of school archive management. SIPARDI was designed as a solution to provide a platform that allows schools to store, search, and manage archives efficiently. This research uses research and development methods (Research and Development, R & D). Namely, analyzing potential and problems, collecting data, designing products, product testing, design revisions, and design validation. Additionally, data was collected through two main approaches. First, literature study to support the product development process. The information and articles collected in the literature study came from various main sources, such as books, journals, internet articles and related research. Second, data was collected through observation and interviews via online Google Meet. The research subjects were teachers and staff. Through collaboration between the development team and related parties at Jenderal Sudirman High School, various features and functions required by the school have been identified and integrated into SIPARDI. SIPARDI's main features include incoming mail, outgoing mail, and disposition modules, which enable schools to record and manage all communications incoming and outgoing from the institution. In addition, the system is equipped with a powerful search feature, which allows users to easily find the required archives. The results of this research show that the level of effectiveness of the SIPARDI web is so that the implementation of the SIPARDI web can be the right solution in the transition of school archives